Bieguny antaganizmów. Europejskie strefy NO-GO - Olszewski, Bogusław (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2017)
The purpose of following article is to analyze the effects of the policy of integration of Muslims in selected Western European countries. So far, the strategy pursued by the governments of Great Britain, the Netherlands, Sweden and France, does not work out, resulting in ever deeper cultural dissection and separation of areas actually excluded from their jurisdiction. No-go zones, which in France alone (ie. Zones urbaines sensibles) are a few hundred, are evidence of the failure of the models of a multicultural society and integration. In face of the current migration crisis, the issue of their re-evaluation and verification appears to have the highest priority, especially that attempts to solve the problems generated by involve an increase in social tension and a potential escalation of violence.
Keywords: Western Europe; no-go zones; integration policy; crime; Islam